Valuable Starting Point for Designing Place-Based Community Engagement - Laura C. Atkins (The University of Alabama, 2022)
A review of the book: Erica K. Yamamura and Kent Koth, Place-Based Community Engagement in Higher Education: A Strategy to Transform Universities and Communities. Sterling, VA: Stylus, 2018, 176 pages. ISBN: 978-1620366776